2012
DOI: 10.15760/trec.24
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating the HSM Predictive Methods for Oregon Highways

Abstract: The Highway Safety Manual (HSM) was published by the American Association of State Highway and Transportation Officials (AASHTO) in the spring of 2010. Volume 2 (Part C) of the HSM includes safety predictive methods which can be used to quantitatively estimate the safety of a transportation facility. The resulting information can then be used to provide guidelines to identify opportunities to improve transportation safety. The safety performance functions (SPFs) included with this content, however, were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The TTI team members ultimately recommended the use of the compass method for providing more reliable and repeatable signing results combined with the corridor truck speeds as indicated above. Dixon and Rohani (2008). Figure 3.1 demonstrates the site sampling procedure developed for this previous research effort.…”
Section: Recent Advisory Speed Researchmentioning
confidence: 99%
“…The TTI team members ultimately recommended the use of the compass method for providing more reliable and repeatable signing results combined with the corridor truck speeds as indicated above. Dixon and Rohani (2008). Figure 3.1 demonstrates the site sampling procedure developed for this previous research effort.…”
Section: Recent Advisory Speed Researchmentioning
confidence: 99%
“…Several of the variables are often unavailable in most of the agencies' databases. During the process of deriving calibration factors for different jurisdictions, several studies identified data collection efforts as one of the most challenging tasks [2,[4][5][6]. Collecting and maintaining all the data variables on the entire road network for the purpose of the HSM implementation are not considered cost feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of sites varied by years, the sample size used in the study exceeded the HSM's minimum recommended criteria. Dixon et al (2012) developed calibration factors to apply the HSM predictive method in the state of Oregon. Calibration factors were determined for all the segment and intersection types discussed in the HSM, using three years (2004)(2005)(2006) of crash data.…”
Section: North Carolinamentioning
confidence: 99%
“…Based on the other states' practices on the selection of minimum segment length (Srinivasan et al, 2011 andDixon et al, 2012), segments shorter than 0.04 miles were not considered in the analysis.…”
Section: Generation Of Homogeneous Segmentsmentioning
confidence: 99%